2009
DOI: 10.1111/j.1600-051x.2008.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Does placement of a connective tissue graft improve the outcomes of coronally advanced flap for coverage of single gingival recessions in upper anterior teeth? A multi‐centre, randomized, double‐blind, clinical trial

Abstract: Both treatments were effective in providing a significant reduction of the baseline recession and dentine hypersensitivity, with only limited intra-operative and post-operative morbidity and side effects. Adjunctive application of a CTG under a CAF increased the probability of achieving CRC in maxillary Miller Class I and II defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
229
4
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(273 citation statements)
references
References 40 publications
30
229
4
10
Order By: Relevance
“…A meta-analysis of CPF and CTG revealed that the mean percentage of root coverage and mean percentage of patients with complete root coverage following CPF were 80% and 50%, respectively, while the corresponding values for CTG were 86% and 61%, respectively, indicating the superiority of CTG 10) . Cortellini et al 4) compared the clinical outcomes of CPF and CTG in single Miller Class I and II gingival recession in a multicenter, double-blind, randomized-controlled clinical trial and similarly concluded that CTG increased the probability of achieving complete root coverage.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of CPF and CTG revealed that the mean percentage of root coverage and mean percentage of patients with complete root coverage following CPF were 80% and 50%, respectively, while the corresponding values for CTG were 86% and 61%, respectively, indicating the superiority of CTG 10) . Cortellini et al 4) compared the clinical outcomes of CPF and CTG in single Miller Class I and II gingival recession in a multicenter, double-blind, randomized-controlled clinical trial and similarly concluded that CTG increased the probability of achieving complete root coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews summarize the results, which may vary regarding complete root coverage (CRC), depending on the surgical technique applied (Roccuzzo et al 2002;Oates et al 2003;Clauser et al 2003;Pagliaro et al 2003;Cairo et al 2008;Chambrone et al 2009;Chambrone et al 2012;Cairo et al 2014). The best results regarding CRC have been reported for the combination of a coronally advanced flap with an underlying connective tissue graft (CTG) (Cortellini et al 2009). It may be speculated that the CTG, firmly sutured to the neighbouring periosteum or gingiva, may positively influence the mechanical properties of the wound and stabilize the mucosal flap by improving blood clot adhesion and maturation on the avascular dentinal surface.…”
Section: Accepted Articlementioning
confidence: 99%
“…La mayoría de los tratamientos en las recesiones gingivales dan resultados predecibles en recesiones clase I y II de Miller con el uso de CDC por sí solo o con el uso de injertos. La literatura también reporta una amplia variación para el parámetro clínico de cubrimiento radicular, con rangos que van entre el 70 al 98% 1,2,3,8,12,14,15 . Es aquí donde la membrana de fibrina podría ser una opción interesante como injerto, debido a la gran cantidad de factores de crecimiento, que cumplirían un rol crucial en la regeneración tisular 6,8,14,13 .…”
Section: Bibliografía Discusiónunclassified
“…conclusión El presente caso clínico muestra que el uso de CDC+ITC en una recesión gingival tipo I de Miller resulta ser un tratamiento predecible y de primera elección para la cobertura radicular tanto en función como estética 1,2,3,11,12,14,15 , si se compara con un CDC+L-PRF. El uso de CDC+L-PRF es una técnica que muestra la ventaja de un menor dolor postoperatorio 7 , se evita la intervención de la zona donante y se obtienen valores clínicos aceptables, pero los resultados en nuestro caso clínico no fueron similares al sitio donde se usó un ITC.…”
Section: Bibliografía Discusiónunclassified